Intern insider : getting the most out of your internship in the entertainment field - Trujillo, Tammy (Routledge, Taylor & Francis Group, 2016)
Internships have all but became a requirement when starting out in the fields of entertainment and broadcasting. Students need these internships not only to get their foot in the door, but to gain valuable experience that gives them an advantage when going for that first job in the industry. Intern Insider helps students navigate the often daunting task of finding an internship, and equips readers to use the experience learned to begin a strong career in the entertainment world. As both a professional broadcaster and college professor, author Tammy Trujillo approaches the topic of internships from both sides: what the student and intern site hope to gain. She provides various valuable perspectives throughout the book, including student assessments on their internship experiences, case studies of those who have turned their internships into careers, and interviews with internship site coordinators. Her breadth of knowledge and experience make for a ground-level book both informative and useful. In the competitive landscape of today's entertainment and broadcasting worlds, Intern Insider provides students with all the tools they need to make the most of their internships and jumpstart their careers! Also visit http://www.interninsider-thebook.com